When Southern women cook : history, lore, and 300 recipes with contributions from 70 women writers - Tipton-Martin, Toni; Bolling, Morgan; Bolling, Morgan; Hysmith, K. C. (Katherine C.); Hysmith, K. C. (Katherine C.); Madadian, Sacha (America's Test Kitchen, 2024)
"Shepherded by Toni Tipton-Martin and Cook's Country Executive Editor and TV personality Morgan Bolling, When Southern Women Cook showcases the hard work, hospitality, and creativity of women who have given soul to Southern cooking from the start. Every page amplifies their contributions, from the enslaved cooks making foundational food at Monticello to Mexican Americans accessing sweet memories with colorful conchas today"--